2022
DOI: 10.1177/02601060221114230
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported consumption frequency of meat and fish products among young adults in Kazakhstan

Abstract: Background: Meat and dairy products are important ingredients in Kazakhstan, although there are indications that high consumption of red and processed meat is associated with a risk of several non-communicable diseases and has an adverse impact on the environment. Aim: The aim of this study was to investigate the dietary habits of young adults in Kazakhstan, particularly meat and fish consumption frequency among university students in five regions of Kazakhstan. Methods: The assessment of meat and fish consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…According to a food frequency survey, conducted in Kazakhstan, fish consumption for fishermen was 103 g/day and 49 g/day for non-fisherman [68], corresponding to 721 and 343 g/week, respectively. These values are higher than the 123 g/week later reported for young adults in Kazakhstan (Table 3) [2]. Jia et al [3] reported the per capita consumption of fish in Kazakhstan of 9.59 kg (184 g/week).…”
Section: Intake Of Fish and Seafood In Central Asiamentioning
confidence: 67%
See 1 more Smart Citation
“…According to a food frequency survey, conducted in Kazakhstan, fish consumption for fishermen was 103 g/day and 49 g/day for non-fisherman [68], corresponding to 721 and 343 g/week, respectively. These values are higher than the 123 g/week later reported for young adults in Kazakhstan (Table 3) [2]. Jia et al [3] reported the per capita consumption of fish in Kazakhstan of 9.59 kg (184 g/week).…”
Section: Intake Of Fish and Seafood In Central Asiamentioning
confidence: 67%
“…This makes fish and seafood an exclusive source of EPA and DHA. However, only a small portion of the population in Central Asia consumes fish in accordance with the nutritional recommendations [2][3][4]. Interestingly, the European Society of Cardiology has classified Kazakhstan as a high-risk country for the development of cardiovascular diseases and Kyrgyzstan and Uzbekistan as very high-risk countries [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the context of the Republic of Kazakhstan, no investigations have been conducted to explore the correlation between cultural dietary habits and COPD. Meat and dairy products hold signi cant importance in Kazakhstan, although there are indications that a high consumption of red and processed meat is linked to an increased risk of various non-communicable diseases and has adverse environmental effects [15]. The outcomes of a study conducted from 2018 to 2023 [15] have contributed to the limited knowledge regarding meat and sh consumption in Kazakhstan.…”
Section: Introductionmentioning
confidence: 99%
“…Meat and dairy products hold signi cant importance in Kazakhstan, although there are indications that a high consumption of red and processed meat is linked to an increased risk of various non-communicable diseases and has adverse environmental effects [15]. The outcomes of a study conducted from 2018 to 2023 [15] have contributed to the limited knowledge regarding meat and sh consumption in Kazakhstan. However, further understanding of dietary patterns and potentially improved recommendations for meat consumption in Kazakhstan are necessary to safeguard public health and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are notable gaps in our understanding of the specific dynamics of food consumption patterns, particularly within the framework of developing economies such as Kazakhstan. Studies on food consumption in Kazakhstan have predominantly concentrated on specific categories like livestock (Liang et al 2020;Akhmetova et al 2022) or fruits and vegetables (Abe et al 2013), with limited attention to overall food consumption. However, there is a lack of recent research, often missing detailed examinations of socioeconomic variables affecting food consumption, especially in the aftermath of geopolitical conflicts and economic shocks.…”
Section: Introductionmentioning
confidence: 99%